NMC411 : Principles of animated content / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2025)
This course introduces the student to the basic theory and concepts of animation. Students will be introduced to the 12 basic principles of animation as outlined by Disney’s nine old men since 1930’s and utilized as an important element used by the animation masses throughout the world either in 2D animation or 3D animation. Emphasis will be on the processes involved in creation of animation looking at the pipeline process of 2D and 3D animation. Study of the history of animation and terminology will be taught as well as to outlay the foundation on how 2D and 3D animation developed through its rich history around the world. Students will then develop skills within the various fields of animation in terms of traditional hand drawn to computer graphics and also the animation software as the medium as well as sketching and drawing at the initial stages of the course.